Influence of Statin Therapy on Exacerbation Frequency in Patients with Chronic Obstructive Pulmonary Disease - (:unkn) unknown (BILIMSEL TIP PUBLISHING HOUSE, 2017)
OBJECTIVES: Chronic obstructive pulmonary disease (COPD) is an inflammatory disease, in which chronic and systemic inflammation plays an important role. By decreasing neutrophil infiltration and cytokine production, statins have anti-inflammatory mechanisms. MATERIALS AND METHODS: Fifty-seven patients who had diagnosis of chronic obstructive pulmonary disease according to GOLD guideline were included in the study; 20 of them were statin users. Statin users group were patients being under medication with regular simvastatin, atorvastatin or rosuvastatin 20 mg per day for at least the past 1 year. RESULTS: There was statistically no significant difference between patients with or without statin treatment with respect to; age, female-male ratio, COPD severity level, medication used for COPD, pulmonary function tests results and smoking habits. COPD exacerbation frequency in patients using statins was significantly less than patients not using statins (p<0.05). Patient number with COPD exacerbation, antibiotic treatment and outpatient clinic administration and outpatient clinic administration frequency was significantly lower in statin using patients (p<0.05). CONCLUSION: COPD patients receiving statins have a lower frequency of COPD exacarbations, hospital administration and antibiotic treatment compared to patients not receiving statins.
Keywords: Statin; COPD; exacerbations; SYSTEMIC INFLAMMATION; LUNG-FUNCTION; COPD; MORTALITY; RISK; METAANALYSIS; CLEARANCE; MORBIDITY